Nanocomposite containing CaF(2) nanoparticles: Thermal cycling, wear and long-term water-aging - Weir, Michael D. (2012)
OBJECTIVES: Fluoride (F) releasing dental restoratives are promising to promote remineralization and combat caries. The objectives of this study were to develop nanocomposite containing calcium fluoride nanoparticles (nCaF(2)), and to investigate the long-term mechanical durability including wear, thermal-cycling and long-term water-aging behavior. METHODS: Two types of fillers were used: nCaF(2) with a diameter of 53 nm, and glass particles of 1.4 μm. Four composites were fabricated with fillers of: (1) 0% nCaF(2) + 65% glass; (2) 10% nCaF(2) + 55% glass; (3) 20% nCaF(2) + 45% glass; (4) 30% nCaF(2) + 35% glass. Three commercial materials were also tested. Specimens were subjected to thermal-cycling between 5 °C and 60 °C for 10(5) cycles, three-body wear for 4×10(5) cycles, and water-aging for 2 years. RESULTS: After thermal-cycling, the nCaF(2) nanocomposites had flexural strengths in the range of 100-150 MPa, five times higher than the 20-30 MPa for resin-modified glass ionomer (RMGI). The wear scar depth showed an increasing trend with increasing nCaF(2) filler level. Wear of nCaF(2) nanocomposites was within the range of wear for commercial controls. Water-aging decreased the strength of all materials. At 2 years, flexural strength was 94 MPa for nanocomposite with 10% nCaF(2), 60 MPa with 20% nCaF(2), and 48 MPa with 30% nCaF(2). They are 3-6 fold higher than the 15 MPa for RMGI (p < 0.05). SEM revealed air bubbles and cracks in a RMGI, while composite control and nCaF(2) nanocomposites appeared dense and solid. SIGNIFICANCE: Combining nCaF(2) with glass particles yielded nanocomposites with long-term mechanical properties that were comparable to those of a commercial composite with little F release, and much better than those of RMGI controls. These strong long-term properties, together with their F release being comparable to RMGI as previously reported, indicate that the nCaF(2) nanocomposites are promising for load-bearing and caries-inhibiting restorations.